Transition towards circular economy: Exploiting open innovation for circular product development - Juan I. Dorrego-Viera; Andrea Urbinati; Valentina Lazzarotti (Journal of Innovation & Knowledge)
Product innovation is a relevant aspect to consider when transitioning towards a circular economy. However, product innovation encounters several barriers that must be overcome. This article explores how companies exploit open innovation practices to overcome barriers while developing circular products. To address this research gap, the study employs a multiple case-study approach of four companies in the manufacturing sector. Two of them operate in European industrialized regions, and other two operate in less developed regions of South America, emphasizing the need for context-specific approaches to circular economy implementation and circular product development. Our results show that, among other barriers, technical ones, including material quality concerns and a lack of skills, represent significant obstacles in both contexts. In addition, among the open innovation practices, the inbound ones, such as sourcing external knowledge and ideas, support companies to overcome these technical challenges, by leading to more innovative and higher-quality products, enhanced reputation, collaboration, and cost reduction. Consumer co-creation is especially crucial for stakeholder engagement and aligning practices with sustainability goals. Finally, collaboration with universities mostly benefits highly industrialized regions and is recommended for acquiring essential capabilities for successful circular product development. From a theoretical perspective, our study contributes to emphasize the relationships between circular economy and open innovation, as well as region-specific circular economy challenges. From a managerial perspective, we show how inbound open innovation practices can aid circular economy implementation, fostering external knowledge and innovation.